LOCAL WISDOM AND CULTURAL VALUES IN AL-AZHAR TAFSIR - Husnel Anwar; Mhd. Roihan Nasution; Muhammad Doli Zamzami Siregar (UIN Sumatera Utara Medan, 2020)
Abstract The problem of this research is how can the local cultural values in Al-Azhar Tafsir. The purpose of this research is knowing local culture values in Al-Azhar Tafsir and analyzing the purpose of HAMKA putting local cultural values ini Al-Azhar Tafsir. The method of this research is library research and uses a study approach of character studies andcontent analytics. Researchers found that HAMKA's attitude was divided into two in linking local cultural values in Al Azhar's Tafsir. First, wanting to preserve local cultural values such as Aphorism, Verse, Poetry, Parable, Pameo and others. The second, strongly opposed and warned people of traditions that were contrary to Islamic Shari'a such as